About some legal problems of protection and use of transboundary water resources between Kazakhstan and China (Journal of actual problems of jurisprudence, 2019)
Cooperation between the countries for the joint operation of transboundary water resources gains the vital value in the modern world. Interdependence in shared water use is characterized by the uneven distribution of water resources, as well as their inefficient use. The article analyzes the situation in the sphere of use and protection of the water resources of the transboundary rivers that have developed between Kazakhstan and China. Attention is paid to the factors influencing the formation and implementation of China’s policy in the use of water resources, examining the ecological and economic consequences of the use of China’s transboundary rivers, and the regulatory framework governing water relations between the two countries. Contract and legal basis of use of transboundary watercourses between two countries are a number of the accepted bilateral agreements. At the present stage there is a need of formation of new legal base for the sphere of the water management relations between Kazakhstan and China. It demands new approaches of two countries in questions of water division and water use, in the solution of problems of protection and use of waters of the transboundary rivers and also strict compliance of bilateral agreements in the water sphere and projects of construction of hydrotechnical objects on transboundary watercourses to rules of international law.Key words: transboundary water resource, water reservoir, water intake, water supply, water resources protection.